COVID-19: ramifications in surgical practice (Journal of Patan Academy of Health Sciences, 2020)
Nepal lies between two large countries (India and China) who have reported high incidence of COVID-19. It is only logical that we prepare the best with the limited medical facilities that we have. There are numerous challenges that impact the surgical department and the hospital administration in general. New guidelines are being formulated and updated frequently. The challenge to provide sufficient personal protective equipment, limited finances and need to train staffs are pertinent challenges. A change in the method of treatment and execution has exerted pressure on the surgeons with a need to keep abreast of new developments.We describe the numerous impacts of the COVID-19 on surgical practice, the impact on surgeons, patients, surgical residents and even the hospitals which have led to all “new normal” in surgery.